PENGARUH HAMBATAN SAMPING TERHADAP KECEPATAN DAN VOLUME LALU LINTAS PADA JALAN TIDAK TERBAGI (2/2 UD DAN 4/2 UD) (STUDI KASUS RUAS JALAN GAJAH MADA KOTA MATARAM): The Effect Of Side Friction On Traffic Speed And Volume On Undivided Roads (2/2 UD And 4/2 UD): (Case Study Of Gajah Mada Road, Mataram City) - Rohani, Rohani; Hasyim, Hasyim; Mahendra, Made; Islamiati, Santri (Ganec Swara, 2025)
The Gajah Mada road segmen in Mataram City has high activity, as well as high side obstacles. These side frictions include parked vehicles, pedestrians, non-motorized vehicles and vehicles exiting/entering. The number of side frictions will certainly affect the speed and volume of traffic moving on the undivided road with 2 lanes in 2 directions and 4 lanes in 2 directions on Gajah Mada road section. Therefore, it is necessary to conduct a study aimed at analyzing the effect of side frictions on traffic speed and volume using the MKJI 1997 method. The results of the analysis show that the highest side obstacles occur on the 2/2UD type road on Monday at 07.00-08.00 at 232.5 events /hour with the highest traffic volume of 3314.85 pcu/hour and the highest space mean speed on the 2/2UD type occurs on Saturday at 13.00-14.00 at 32,310 km/hour. Simultaneously and partially (parked vehicles, pedestrians, non-motorized vehicles and vehicles entering/exiting from the side of the road), a very strong influence was obtained between side friction and traffic speed and volume because the dominant correlation coefficient (R) was greater than 0.9 (R > 0.9) on road types 2/2UD and 4/2UD